Oral Health-Related Quality of Life of Children by Dental Caries and Fluorosis Experience - Loc G. Do, PhD; A. Spencer, PhD (Blackwell Synergy, 2007)
To evaluate the oral health-related quality of life (OHRQoL) of children by dental caries and fluorosis status.